PELESTARIAN BUDAYA RONDA DAN JIMPITAN DALAM PENINGKATAN SISTEM KEAMANAN LINGKUNGAN DI MANDAN SUKOHARJO - SRI RIRIS (Adi Widya : Jurnal Pengabdian Masyarakat, 2022)
The number of crimes that are currently rife during the Covid-19 pandemic in the Mandan community has made people restless. The patrol activity is seen as an activity that is quite effective in minimizing the crime of theft. However, these activities have begun to be abandoned because of the busyness of the community. This community service provides insight into the importance of preserving the ronda and jimpitan culture in improving the environmental security system. The patrol activity, which is followed by the ‘jimpitan activity, provides the benefits of maintaining environmental security and the results of the pinch can increase cash to support social activities. Social activities that are supported from the results of collecting jimpitan, for example. community service activities, procurement of street lighting lampposts, tirakatan 17's and other activities that are for the common interest.